Adaptation of Carbon Source Utilization Patterns of Geobacter metallireducens During Sessile Growth - Marozava, Sviatlana; Merl-Pham, Juliane; Müller, Hubert; Meckenstock, Rainer U. (Frontiers in Microbiology, 2020)
There are two main strategies known how microorganisms regulate substrate utilization: specialization on one preferred substrate at high concentrations in batch cultures or simultaneous utilization of many substrates at low concentrations in chemostats. However, it remains unclear how microorganisms utilize substrates at low concentrations in the subsurface: do they focus on a single substrate and exhibit catabolite repression or do they de-repress regulation of all catabolic pathways? Here, we investigate the readiness of Geobacter metallireducens to degrade organic substrates under sessile growth in sediment columns as a model for aquifers. Three parallel columns were filled with sand and flushed with anoxic medium at a constant inflow (18 ml h-1) of the substrate benzoate (1 mM) with non-limiting nitrate concentrations (30 mM) as electron acceptor. Columns were inoculated with the anaerobic benzoate degrader G. metallireducens. Microbial degradation produced concentration gradients of benzoate towards the column outlet. Metagenomics and label-free metaproteomics were used to detect and quantify the protein expression of G. metallireducens. Bulk benzoate concentrations below 0.2 mM led to an increased abundance of catabolic proteins involved in the utilization of fermentation products and aromatic compounds including the complete upregulation of the toluene-degrading pathway although toluene was not added to the medium. We propose that under sessile conditions and low substrate concentrations Geobacter metallireducens expresses a specific set of catabolic pathways for preferred substrates, even when these substrates are not present.